An Analysis of Word Formation Processes Found in TikTok Application - Iffah Al Hikmah; Hamzah Machmoed; Harlinah Sahib (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research explores the process of words formation and its impact on the part of speech of words in data words formation processes. This research used descriptive qualitative data, by using observation and capturing the data. Data source in this study is TikTok of Charli Grace D’Amelio. The data in this research are taken from the captions, hastags, and comments or words that consist of morphological process in TikTok of Charli Grace D’Amelio. The researcher used the theory of Delahunty and Garvey (2010) and Plag (2003) which divides word formation into 8 types these are compounding, abbreviation, blending, affixation, coinage, conversion, acronyms, and borrowing. The result of the data showed that the researcher found 11 words formation of compounding, 7 words formation of abbreviation, 2 words formation of blending, 8 words formation of affixation, 7 words formation of coinage, 8 words formation of conversion, 16 words formation of acronyms, and 2 words formation of borrowing. The data findins and analysis from Charli Grace D’Amelio TikTok page indicate a predominant use of acronyms in word formation processes. The researcher presumed that the implementation of word formation by the users of TikTok inform that sometimes they wrote something inappropriate way such as acronym. They wrote them in lowercase other than to be written in uppercase. TikTokers tend to ignore the rule of word formation. It can be concluded that the aim of different types of word formation processes assisted people to understand the function of each word formation processes in order to avoid mistake in their writing. People have to use types of word formation processes which depend on their functions.